2014
DOI: 10.1016/j.tjog.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of laparoscopic sacrocolpopexy and total vaginal mesh procedure using lightweight polypropylene meshes for prolapse repair

Abstract: POP repair by LSC or TVM using the new lightweight polypropylene meshes seems to be safe and has comparable outcomes, but limitations may vary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 32 publications
5
41
1
Order By: Relevance
“…On the other hand, increasing rates of vaginal hysterectomy from Prosima to Elevate repairs were due to changing policy for managing prolapsed (POP ≧stage 2) uterus. In our previous studies, we found the preservation of a prolapsed (POP ≧stage 2) uterus during the Prosima procedure or a transvaginal trocar‐guided mesh repair using partially absorbable meshes (Prolift + M) contributed to higher rates of anatomic recurrence. Long et al found similar results that advanced uterine prolapse was one significant predictor of failure following trocar‐guided transvaginal mesh reapir for POP .…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, increasing rates of vaginal hysterectomy from Prosima to Elevate repairs were due to changing policy for managing prolapsed (POP ≧stage 2) uterus. In our previous studies, we found the preservation of a prolapsed (POP ≧stage 2) uterus during the Prosima procedure or a transvaginal trocar‐guided mesh repair using partially absorbable meshes (Prolift + M) contributed to higher rates of anatomic recurrence. Long et al found similar results that advanced uterine prolapse was one significant predictor of failure following trocar‐guided transvaginal mesh reapir for POP .…”
Section: Discussionmentioning
confidence: 97%
“…The aim of this study was to make a retrospective comparison of TVM and LSC for pelvic floor reconstruction, with a long‐term follow‐up to evaluate their effects and safety. Few studies have compared the two methods directly . The results show that intraoperative bleeding was less in the LSC group, but the operation time was longer.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the postoperative recurrence rates were 8.5% for TVM and 5.1% for LSC, without significant difference. These results were similar to those of a previous study …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations